THE ANNUNCIATION IN PAUL CONSTANTINESCU´S CHRISTMAS ORATORIO: MUSICAL AND ICONOGRAPHIC DECODING - ŢIPLEA TEMEŞ, Bianca (Studia Universitatis Babes-Bolyai Musica, 2010)
This study engages in hermeneutics to offer a set of decoding clues regarding the integration of the Byzantine melos into Paul Constantinescu’s creation. Nowadays, the author is regarded as a forerunner in the expansion of the psaltic monody beyond its familiar vocal tradition: both his Oratorios transform the Byzantine melodic heritage into a key ingredient of the instrumental genres. The musical rendering of the Annunciation (opening part of the Christmas Oratorio), serves as an ideal symbiotic model between traditional hymnography and the modern composition techniques of that time. By adopting authentic sources from Macarie, Suceveanu, Stupcanu, Anton Pann, but also by interfacing music with the ekphonetic cantillation of the annunciation pericope (Panţîru – Iaşi Evangelic Lectionary), Paul Constantinescu seems to assume the role of an “iconographer”: respecting the canonical norm at the melodic level while accessorising music with personal exterior elements. The Annunciation segment also admits a symbolic decoding: it prepares the birth of a superior integrative vision promoted by the Romanian composers of the next generations, ushering in a new assimilation stage of the Byzantine chant.